Sorafenib and azacitidine as salvage therapy for relapse of FLT3‐ITD mutated AML after allo‐SCT. (2nd February 2017) - Rautenberg, Christina; Nachtkamp, Kathrin; Dienst, Ariane; Schmidt, Pia Verena; Heyn, Claudia; Kondakci, Mustafa; Germing, Ulrich; Haas, Rainer; Kobbe, Guido; Schroeder, Thomas
Abstract: Objective: Patients with acute myeloid leukemia (AML) carrying FLT3‐ITD mutations (FLT3‐ITD+) who relapse after allogeneic transplantation (allo‐SCT) have a very dismal prognosis with the currently available treatment options. Methods: We treated eight patients with FLT3‐ITD+ AML who had relapsed in median 91 d (range, 28–249) following allo‐SCT with a combination of the multikinase inhibitor sorafenib and the DNA methyltransferase inhibitor azacitidine (Aza). Results: Patients received a median of five cycles of Aza (range, 2–9) and sorafenib with a median daily dosage of 750 mg (range 400–800) for 129 d (range, 61–221). Six of eight patients received donor lymphocyte infusions (DLI) with a median number of two DLI per patient (range, 1–4). Following this treatment, four patients (50%) achieved a complete remission and three of them a complete molecular remission. Median duration of CR was 182 d (range, 158–406), and two patients remain in ongoing remission for 406 and 168 d. Median overall survival was 322 d (range, 108–574 d) with three patients being currently alive. Conclusion: Taken together, the combination of sorafenib, Aza, and DLI shows promising efficacy and deserves further evaluation in larger patient groups.